Oxidative Stability, Carcass Traits, and Muscle Fatty Acid and Amino Acid Profiles in Heat-Stressed Broiler Chickens - Mahmoud S. El-Tarabany; Omar A. Ahmed-Farid; Mohamed Abdo Nassan; Ayman S. Salah (MDPI AG, 2021)
The objective was to elucidate the effects of chronic heat stress on carcass traits, muscle oxidative stability, muscle fatty acids and amino acid profiles in broiler chickens. A total of 100-day-old male Ross broiler chicks were divided into two equal groups of five replicates. The control group (TN) was maintained on a thermoneutral condition, while the experimental group (HS) was subjected to 8 h of heat stress (34 °C). The HS group showed lower dressing percentage and breast yield compared with the TN group (p = 0.040 and 0.042, respectively). Meanwhile, heat stress significantly increased the percentage of abdominal fat in broiler chickens (p = 0.001). The HS group showed significantly lower levels of PUFA (linoleic, docosahexaenoic and eicosapentaenoic) in the breast (p = 0.003, 0.002 and 0.001, respectively) and thigh (p = 0.001, 0.009 and 0.003, respectively) muscles than did the TN group. The levels of α-lenolinec acid in the breast and thigh muscles did not differ between both experimental groups (p = 0.818 and 0.060, respectively). With exception of threonine, tyrosine and phenylalanine, the levels of essential AA in the breast muscles were significantly (p ˂ 0.05) reduced in the HS group. The HS group showed significantly higher concentration of malondialdehyde (MDA) in the breast muscles (p = 0.032). Meanwhile, the concentration of MDA in the thigh muscles did not differ between both experimental groups (p = 0.149). Furthermore, the HS group showed significantly lower superoxide dismutase and catalase in heart tissues (p = 0.005 and 0.001, respectively). In conclusion, chronic thermal stress deteriorates carcass yield and the oxidative stability of breast muscles, as well as the levels of PUFA and essential AA in broiler chickens. However, the oxidative stability of thigh muscles was not affected.